The shift of superstitious behavior: Do The Balinese believe in lucky and unlucky numbers? - Wedayanti, Ni Putu Luhur; Sulatri, Ni Luh Putu Ari; Purnawati, Ketut Widya (e-Journal of Linguistics, 2025)
This study is motivated by the avoidance of unlucky numbers in some areas of Bali. This is not in line with the beliefs of Balinese people who generally don’t believe in unlucky numbers. This study aims to analyze the causes of the phenomenon using a qualitative research approach. Data were collected using direct observation, questionnaires, and interview responses. The results of the data analysis show that there are groups of people who know of the existence of unlucky numbers, but only a small proportion believe in it. The phenomena of unlucky number avoidance could be concluded as a business strategy.